Engineering materials 1: an introduction to properties, applications, and design - Ashby, Michael F.; Jones, David R. H.
Widely adopted around the world, Engineering Materials 1 is a core materials science and engineering text for third- and fourth-year undergraduate students; it provides a broad introduction to the mechanical and environmental properties of materials used in a wide range of engineering applications. The text is deliberately concise, with each chapter designed to cover the content of one lecture. As in previous editions, chapters are arranged in groups dealing with particular classes of properties, each group covering property definitions, measurement, underlying principles, and materials selection techniques. Every group concludes with a chapter of case studies that demonstrate practical engineering problems involving materials. Engineering Materials 1, Fourth Edition is perfect as a stand-alone text for a one-semester course in engineering materials or a first text with its companion Engineering Materials 2: An Introduction to Microstructures and Processing, in a two-semester course or sequence. New and Key Features Include: Many new design case studies and design-based examples Revised and expanded treatments of stress-strain, fatigue, creep, and corrosion Additional worked examples-to consolidate, develop, and challenge Compendia of results for elastic beams, plastic moments, and stress intensity factors Many new photographs and links to Google Earth, websites, and video clips Accompanying companion site with access to instructors? resources, including a suite of interactive materials science tutorials, a solutions manual, and an image bank of figures from the book